2010
DOI: 10.1002/cm.20443
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of VASP phosphorylation in the regulation of chemotaxis and osmotic stress response

Abstract: VASP plays crucial roles in controlling F-actin-driven processes and growing evidence indicates that VASP function is modulated by phosphorylation at multiple sites. However, the complexity of mammalian system prevents the clear understanding of the role of VASP phosphorylation. In this study, we took advantage of Dictyostelium which possesses only one member of the Ena/VASP family to investigate the functional roles of VASP phosphorylation. Our results demonstrated that hyperosmotic stress and cAMP stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This is not particularly surprising given that cell movement is a complex and cell type–dependent process and that VASP is involved in many actin-dependent processes ( Bear and Gertler, 2009 ). In contrast to random cell migration, little is known about the role of VASP in chemotaxis, and most studies were conducted either in slime mold ( Han et al, 2002 ; Lin et al, 2010 ) or in cell lines overexpressing chemokine receptors ( Neel et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is not particularly surprising given that cell movement is a complex and cell type–dependent process and that VASP is involved in many actin-dependent processes ( Bear and Gertler, 2009 ). In contrast to random cell migration, little is known about the role of VASP in chemotaxis, and most studies were conducted either in slime mold ( Han et al, 2002 ; Lin et al, 2010 ) or in cell lines overexpressing chemokine receptors ( Neel et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The actin regulatory functions of VASP are highly sensitive to salt concentrations, which suggests that the phosphorylation of VASP could dramatically affect the actin regulatory activity. Of the three VASP conservative phosphorylation sites (Ser-157, Ser-239, and Thr-278), only the phosphorylation of Ser-157 led to a shift in the apparent molecular mass from 46 to 50 kDa, indicating that this phosphorylation might cause a change in the secondary structure of the molecule [26,27] . Our data showed that the far-UV CD spectra that corresponded to the VASP secondary structure were sensitive to the concentration of matrine.…”
Section: Discussionmentioning
confidence: 99%
“…39,41 DdVASP expression occurs in vegetative cells and increases with starvation peaking at 8 h. 39 Phosphorylation of VASP is important for its cortical localization and interaction with WASP and WIPa that are key regulators of F-actin organization. 42 Lin and co-workers 42 showed that VASP phosphorylation still occurs in Dictyostelium null strains of the PKA catalytic domain ( pka-cat À ) and of guanylyl cyclases (sgc/gca À ). Furthermore, no VASP phosphorylation was observed in cells treated with membranepermeable derivatives of cAMP and cGMP.…”
Section: Discussionmentioning
confidence: 99%